INCLUSIVE EDUCATION: NECESSITY, PROSPECTIVE TREND - Abdullayev Jahangir; Botirov Shonazar (Journal of Learning on History and Social Sciences, 2024)
This article describes the introduction of inclusive education, what it is, about children with disabilities, as well as the positive and negative aspects of inclusive education.